(untitled) (Revista BOEM, 2025)
The article analyzes the reflection concerning teaching mobilized in a lesson study that involved mathematics teachers. The research bases on the reflection concept of Shön and Perrenoud, was guided by the question: What reflections concerning teaching are mobilized by mathematics teachers in the lesson study context? The investigation was carried out in the context of a lesson study, structured in 12 meetings of approximately 2.5 hours each, which involved eight Mathematics teachers from the final years of elementary school, belonging to the state public education system in the Rio Grande do Sul. The empirical material of the research consists of the researcher’s field notes, the participants’ logbooks, the transcripts of the sessions, and an interview carried out at the end of the class study. The analysis, qualitative and interpretive, showed that that the reflection on teaching was retrospective and prospective, covering three themes: student learning, mathematics teaching, moral responsibility and teaching ethics.